2021
DOI: 10.2196/20131
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Telemonitoring in Managing the COVID-19 Pandemic: Pilot Implementation Study

Abstract: Background Most people with COVID-19 self-manage at home. However, the condition can deteriorate quickly, and some people may develop serious hypoxia with relatively few symptoms. Early identification of deterioration allows effective management with oxygen and steroids. Telemonitoring of symptoms and physiological signs may facilitate this. Objective The aim of this study was to design, implement, and evaluate a telemonitoring system for people with CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Community-based telemonitoring of symptoms scores, temperature, oximetry, and blood pressure supported by self-management information and/or remote monitoring proved to be a cost-effective alternative to hospitalisation. [15,16,18,[154][155][156][157][158] Although a rapid systematic review was unable to confirm safety due to lack of standardised reporting, [18] mixed-method evaluation of individual programmes concluded that they were reassuring to patients (especially the oximetry), [15,155,158] acceptable to clinicians, [15,154,158] able to detect signs of deterioration, [15,158,159] and a safe approach for selected high-risk patients with mild-to-moderate COVID-19. [15,16,18,[157][158][159] Economic analysis was limited to reporting resources used and the amount spent per patient monitored.…”
Section: Digital Innovation To Manage Covid-19 Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community-based telemonitoring of symptoms scores, temperature, oximetry, and blood pressure supported by self-management information and/or remote monitoring proved to be a cost-effective alternative to hospitalisation. [15,16,18,[154][155][156][157][158] Although a rapid systematic review was unable to confirm safety due to lack of standardised reporting, [18] mixed-method evaluation of individual programmes concluded that they were reassuring to patients (especially the oximetry), [15,155,158] acceptable to clinicians, [15,154,158] able to detect signs of deterioration, [15,158,159] and a safe approach for selected high-risk patients with mild-to-moderate COVID-19. [15,16,18,[157][158][159] Economic analysis was limited to reporting resources used and the amount spent per patient monitored.…”
Section: Digital Innovation To Manage Covid-19 Infectionsmentioning
confidence: 99%
“…[15,16,18,[154][155][156][157][158] Although a rapid systematic review was unable to confirm safety due to lack of standardised reporting, [18] mixed-method evaluation of individual programmes concluded that they were reassuring to patients (especially the oximetry), [15,155,158] acceptable to clinicians, [15,154,158] able to detect signs of deterioration, [15,158,159] and a safe approach for selected high-risk patients with mild-to-moderate COVID-19. [15,16,18,[157][158][159] Economic analysis was limited to reporting resources used and the amount spent per patient monitored. [18] Contact tracing smartphone-based applications potentially helped control the spread of COVID-19, but the effectiveness of this technology depends on high levels of adoption among the population.…”
Section: Digital Innovation To Manage Covid-19 Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the design of these studies precluded the determination of what percentage of repeat visits were related to COVID-19 or what factors may have been responsible for the high rate of return (e.g., worsening symptoms, inadequate follow-up, and anxiety). Nonetheless, efforts have been made to monitor patients remotely in the hope of identifying those with evidence of disease progression, and therapeutic strategies have targeted "high-risk" patients discharged from the ED in an effort to reduce subsequent hospitalization [10][11][12]. A better understanding of symptom progression in these patients and the impact of various demographics and/or comorbidities might improve these efforts and assist providers caring for these patients following an ED visit.…”
Section: Introductionmentioning
confidence: 99%
“…4 These results suggest a role for FDA-approved pulse oximeters in both remote monitoring and triaging of COVID-19 infected outpatients. There have been a variety of remote monitoring studied for COVID, 5,6 though few have assessed patient experience.…”
Section: Introductionmentioning
confidence: 99%